2007
DOI: 10.1345/aph.1h686
|View full text |Cite
|
Sign up to set email alerts
|

Patients' Use and Perception of Medication Information Leaflets

Abstract: Approximately two-thirds of the patients surveyed reported reading the leaflets provided with new medications at least often. The majority reported the leaflets to be useful and easy to understand. Pharmacists should advocate reading the leaflet and promote it as a useful resource. The leaflet should not replace the pharmacist's obligation to provide verbal counseling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 8 publications
4
52
1
2
Order By: Relevance
“…19 Nearly one third of patients do not read leaflets provided with new medications. 20 Furthermore, verbal prescription counseling by pharmacists, although meeting minimum federal and state requirements, is considered neither excellent nor good 21 , and this may have important ramifications for patients with low health literacy. Thus, patients may concurrently use alcohol and AI medications because they are unaware that doing so places them at high risk for harmful interactions.…”
Section: Discussionmentioning
confidence: 99%
“…19 Nearly one third of patients do not read leaflets provided with new medications. 20 Furthermore, verbal prescription counseling by pharmacists, although meeting minimum federal and state requirements, is considered neither excellent nor good 21 , and this may have important ramifications for patients with low health literacy. Thus, patients may concurrently use alcohol and AI medications because they are unaware that doing so places them at high risk for harmful interactions.…”
Section: Discussionmentioning
confidence: 99%
“…However, in UK only 35 % of patient reads PPI completely [9]. Another researcher reported that 49.2 % patients always read PPI and 48.3 % of patients said that they faced problem in understanding PPIs [15]. As majority of the respondents were educated, they were aware of the significance of reading PPI.…”
Section: Discussionmentioning
confidence: 98%
“…Nathan et al [17] befragten amerikanische Patienten anhand eines Fragebogens, ob sie den BPZ eines neuen Medikaments lesen, diesen verstehen und ihn als hilfreich empfinden. Zwei Drittel der Befragten würden den BPZ eines neuen Medikaments immer lesen und diesen auch verstehen und ihn als hilfreich empfinden.…”
Section: Einfluss Des Beipackzettels Auf Die Medikamentöse Therapieunclassified